2017
DOI: 10.1007/s10822-017-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Binding mode prediction and MD/MMPBSA-based free energy ranking for agonists of REV-ERBα/NCoR

Abstract: The knowledge of the free energy of binding of small molecules to a macromolecular target is crucial in drug design as is the ability to predict the functional consequences of binding. We highlight how a molecular dynamics (MD)-based approach can be used to predict the free energy of small molecules, and to provide priorities for the synthesis and the validation via in vitro tests. Here, we study the dynamics and energetics of the nuclear receptor REV-ERBα with its co-repressor NCoR and 35 novel agonists. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…In this paper, GROMACS 4.6.5 software was used to simulate the molecular dynamics (MD) of the ligand complex structures of DEP and its derivatives in Sybyl-x2.0, docked with phthalate dioxygenase reductase, esterase and acid esterase. The Poisson–Boltzmann surface area (MM-PBSA) method was used to calculate the binding free energy in the molecular dynamics [ 53 ]. Compared with the scoring function of molecular docking, the degree of binding energy characterized the biodegradability of DEP molecules before and after modification ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, GROMACS 4.6.5 software was used to simulate the molecular dynamics (MD) of the ligand complex structures of DEP and its derivatives in Sybyl-x2.0, docked with phthalate dioxygenase reductase, esterase and acid esterase. The Poisson–Boltzmann surface area (MM-PBSA) method was used to calculate the binding free energy in the molecular dynamics [ 53 ]. Compared with the scoring function of molecular docking, the degree of binding energy characterized the biodegradability of DEP molecules before and after modification ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Its calculation is based on the MM/PBSA and MM/GBSA approaches starting from the equilibrium energy values obtained through molecular dynamics simulation. Although the calculation does not consider the translational entropy (huge computational cost), it has been shown that it does provide adequate values of the relative binding energies, which have been experimentally validated in biological systems [49,50] and it has recently been reported that when the MM/PBSA and MM/GBSA are used together with empirical corrections, they allow better experimental correlations [51].…”
Section: Discussionmentioning
confidence: 99%
“…Calculated binding free energies have an average standard deviation of 2–3 kcal/mol. However, the MM/PBSA and MM/GBSA methods revealed as very useful in predicting a ranking of activity against biological systems and have been successfully validated experimentally [34]. These methods have been used to provide a relatively quick estimate of the nanotube activity ranking for DOX encapsulation with consistent results, comparable to other sources and prove to be quite useful if the actual value of the binding free energy is not required [18].…”
Section: Discussionmentioning
confidence: 99%
“…The drug (ligand)-nanotube (receptor) binding free energies were determined through the complementary methods MM/PBSA and MM/GBSA implemented in AMBER [36]. In spite that MM/PBSA typically gives too large energies it is recognized as useful in rationalizing experimental and theoretical findings [18,34,41]. These methods were applied on an ensemble of 200 uncorrelated snapshots collected from the equilibrated molecular dynamics simulation and were performed considering ΔG=GDOXCNTGCNTGDOXDOXCNT where G DOX-CNT , G CNT , and G DOX correspond to the Gibbs free energy terms for the DOX-CNT complex, the receptor and the ligand, respectively.…”
Section: Methodsmentioning
confidence: 99%